Ovicidal effects of entomopathogenic fungal isolates on the invasive Fall armyworm Spodoptera frugiperda (Lepidoptera: Noctuidae) - Akutse, Komivi Senyo; Kimemia, Jane Wanjiru; Ekesi, Sunday; Khamis, Fathiya Mbarak; Ombura, Odhiambo Levi; Subramanian, Sevgan (Journal of applied entomology (1986), 2019)
Maize is a major staple food for over 300 million people in sub‐Saharan Africa. Sustainable productivity of this primary crop has been recently threatened by Fall armyworm (FAW), Spodoptera frugiperda invasion. Due to lack of environmentally safe management strategies, immediate responses by growers and governments to tackle FAW are based on rampant use of pesticides. Looking for efficient biopesticides, twenty entomopathogenic fungal isolates (14 Metarhizium anisopliae and 6 Beauveria bassiana) were screened for their efficacy against eggs and second instar larvae of FAW. A single discriminating concentration of 1 × 108 conidia ml−1 and four replicates per treatment were used in all experiments. Isolates were assessed for their ability to cause mortality of FAW second instar larvae, eggs and the neonate larvae that emerged from treated eggs. Among the isolates tested, only B. bassiana ICIPE 676 caused moderate mortality of 30% to second instar larvae. Metarhizium anisopliae ICIPE 78, ICIPE 40 and ICIPE 20 caused egg mortalities of 87.0%, 83.0% and 79.5%, respectively, and M. anisopliae ICIPE 41 and ICIPE 7 outperformed all the others by causing 96.5% and 93.7% mortality to the neonate larvae, respectively. The cumulated mortality of eggs and neonates was highest with M. anisopliae ICIPE 41 (97.5%), followed by M. anisopliae ICIPE 7, 655, 40, 20 and 78 with total mortality of 96.0%, 95.0%, 93.5%, 93.0% and 92.0%, respectively. These isolates with high cumulated mortality (≥92%), especially ICIPE 78 and 7, which are already commercialized for spider mites and ticks control respectively, would be good candidates for development as biopesticides for management of FAW in Africa if further evidence of their efficacy is obtained in the field.